Family Nutrition Improvement Efforts Through Nutrition Management of Pokea Clam Based on Environmental Health - I Putu Sudayasa; Hartati Hartati; Bahtiar Bahtiar (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
The coastal communities of the Pohara river, Sampara Subdistrict, where the habitat for endemic pokea clam growth, has a habit of consuming pokea clam meat which can affect the nutritional status of the family. Pokea clam meat (Batissa violacea celebensis von Marten 1897) contains fatty acids, which can reduce the risk of cardiovascular disease. The purpose of this community service, to identify patterns of consumption of pokea clam and  nutritional status. The method used through interviews, counseling and examination of nutritional status. The number of respondents identified was 72 respondents. Data were collected by questionnaire regarding the consumption pattern of pokea clam, measurement of height, weight and waist circumference. The results of the identification of consumption patterns of pokea clam meat showed 58% of respondents, consuming average pokea clam 1-3 times a day. As many as 78%, processing directly the pokea clam meat. The types of preparations consumed are pokea satay (39%) and boiled pokea (8%). The results of examination of Body Mass Index (BMI) obtained 50.0% normal nutritional status, 16.7% excess and 30.6% obesity. Waist circumference measurement results, 47.2% are normal, and 52.8% are not normal. Integrated and sustainable health promotion, need to improve the nutritional status of coastal communities.